The impact of audit software on quality of audit in Kuwait: Insights from auditors , - Awwad Alnesafi (Accounting)
This research tries to find a relationship between audit quality and audit software, impacted by the latter. In this study, multiple sentiments of audit professionals and finance executives on the relation of audit software and quality of audit in Kuwait are examined where, on the basis of agreed perspectives of professionals, it was found that audit software positively influences audit quality. This particular article tries to extend the previous works and emphasizes on the observation of audit professionals and their perspectives through a well-structured survey and semi-structured interviews. This study is to identify the distinctiveness of the audit industry in Kuwait comparing market size and available inadequate local auditors. The authors try to establish the relationship between audit quality and audit software considering the fact that acceptance of audits software will definitely give a more effective and robust audit process to cover market needs. The paper also considers the auditors’ training and experience as a moderating factor for the adoption and usage of audit software in auditing practices in Kuwait, resulting in useful insights on the effects of the adoption and use of auditing software in enhancing the quality of audit reports as well as suggesting resources for the use of technological developments in auditing practices. Thus, the study contributes to the extant literature on the dynamics for the adoption and usage of computerized systems in auditing practices to improve the quality of audit reports.